2017
DOI: 10.1177/0972150917692064
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining Firm Size-profitability Nexus: Empirical Evidence from Non-financial Listed Firms in Nigeria

Abstract: The bulk of extant studies on the relationship between firm size and profitability focus on the effect of former on the latter, neglecting the possibility of feedback effect. This research work re-examines the direction of causality between firm size and profitability for 63 listed non-financial Nigerian firms for the period 1998–2010, using an innovative econometric methodology of a dynamic panel generalized method of moments to resolve the problem of endogeneity inherent in the relationship. The results esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 40 publications
4
44
0
4
Order By: Relevance
“…It is measured as the natural logarithms of annual pay of the CEOs. Firm performance ( PERF ): A proxy for firm performance adopted in this study is return on assets (ROA). This is measured by profit after tax divided by total assets (Olaniyi et al , ; Outa and Waweru, ; Liang et al , ; Alley et al , ; Obembe et al , ; Ntim et al , ; Abidin et al , ; Duffhues and Kabir, ; Haniffa and Hudaib, ; Zhou, ). Firm size ( FMS ): This is defined in terms of total assets owned by each firm. It is measured by the natural logarithms of total assets of the respective firm.…”
Section: Methodsmentioning
confidence: 99%
“…It is measured as the natural logarithms of annual pay of the CEOs. Firm performance ( PERF ): A proxy for firm performance adopted in this study is return on assets (ROA). This is measured by profit after tax divided by total assets (Olaniyi et al , ; Outa and Waweru, ; Liang et al , ; Alley et al , ; Obembe et al , ; Ntim et al , ; Abidin et al , ; Duffhues and Kabir, ; Haniffa and Hudaib, ; Zhou, ). Firm size ( FMS ): This is defined in terms of total assets owned by each firm. It is measured by the natural logarithms of total assets of the respective firm.…”
Section: Methodsmentioning
confidence: 99%
“…The growth ratios consist of asset growth and sales growth. Olaniyi et al (2017) stated that sales growth has a strategic influence on the company because sales growth is marked by an increase in market share which positively impacts sales of the company and increases the profitability of the company.…”
Section: Financial Ratiomentioning
confidence: 99%
“…Companies with growing profits will have a large number of assets, thus providing greater opportunities to generate profitability (Shahnia et al, 2020). Olaniyi et al, (2017) stated that FS has a significant positive effect on profit growth. The purpose of this study was to partially analyze the effect of CR, CLI, TAT, NPM, SG, and FS on profit growth in F&B companies on the IDX.…”
Section: Introductionmentioning
confidence: 99%
“…These works argue that bank size allows banks to enjoy economies of scale thereby increasing profitability. On the other hand, negative effects of bank size attributed to diseconomies of scale and manifesting in forms of rigidities, inertia, the bureaucracy that characterized big organizations (Athanasoglou et al, 2008; Jakubík & Reininger, 2014; John, 2018; Khemraj & Pasha, 2016; Kjosevski & Petkovski, 2017; Olaniyi, Simon‐Oke, Obembe, & Bolorinwa, 2017; Petria et al, 2015) have been reported. Capitalization is another important determinant in the literature (Kjosevski et al, 2019; Klein, 2013; Kumar & Kishore, 2019).…”
Section: Brief Literature Reviewmentioning
confidence: 99%